e-activity management system (student) for Faculty of Science Computer and Mathematic (FSKM) / Siti Nur Afifah Ismail - Ismail, Siti Nur Afifah (2013)
There are many systems and application has been migrated to the web-based in the world nowadays. At the current system, the entire documents to apply an activity are done by manual. But, when using manual system, it is difficult to manage all the documents and details. The purpose this project is to help the student of FSKM to apply an activity in more proper and systematic way. This project proposed to design and develop the e-activity management system for FSKM. Using this system, students in FSKM can get information about all the activity in FSKM. The system architectures that are used to develop this system are DBTools Manager Professionals, XAMPP Server and PHP. This system will be access with web browser like Mozilla Firefox and managed by the administrator or the staffs. This system will reduce time to manage the component and prevent form data lost.